Life cycle assessment of Ni-alumina and V-alumina catalysts for catalytic oxidative dehydrogenation of ethane - Audrlická Vavrušová, Lenka; Krejčová, Anna; Baťa, Robert; Pouzar, Miloslav (University of Pardubice, 2020)
In this work, the Life Cycle Assessment (LCA) analysis “from the gate to the gate” is used to compare environmental effects of the Ni- or V-alumina catalyst preparation and their use in heterogeneous catalytic oxidative dehydrogenation of ethane (C2-ODH) as the way of ethane production in laboratory conditions. The system boundary was defined as “laboratory production of catalysts and ethylene”, the functional unit set up as “one-year production of ethene under specific laboratory conditions”. The TRACI methodology and ILCD database, as well as laboratory data, were used in the study. The inputs of the product system were found to be higher for the V-alumina, then for Ni-alumina for resources, deposited goods, radioactive waste, and stockpiles. Results of the Life cycle impact analysis (LCIA) revealed worse environmental impacts for the V-alumina in all evaluated end-points. The V-alumina was more demanding in the view of total emission from the product system to the environmental compartments, as groups of emission to air or categories as Global Warming Potential (GWP), Acidification, Ozone Depletion and Human Health Cancer (HHC) parameters. The LCA analysis of the laboratory catalytic dehydrogenation of ethane has indicated that the Ni-alumina is a better choice in terms of environmental impacts.
Keywords: LCA; oxidative dehydrogenation of ethane; Ni-alumina; V-alumina